The Implementation of Qur'an Hadith Learning Using Blended Learning at MTs. DDI Amparita, Tellu Limpoe District, Sidenreng Rappang Regency (Supervised by Muhammad Saleh and Ahdar) - Lukman Kato; Muhammad Saleh; Ahdar; Saepudin; Firman (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This research aims to examine the planning of the blended learning model in Qur'an Hadith education for students at MTs DDI Amparita and to assess its implentation. The research employs a descriptive qualitative approach and was conducted at MTs DDI Amparita in Sidenreng Rappang Regency. Data collection techniques include interviews, observations, and documentation. Data analysis was performed using an interactive qualitative method, involving data reduction, data presentation, and conclusion drawing after verification. The findings indicate the implementation of the blended learning model in Qur'an Hadith education for students at MTs DDI Amparita. The implementation involves preparing learning tools suitable for blended learning, setting up specific media for online learning, and ensuring student engagement and comprehension through interactive questioning during material delivery. The effectiveness of using the blended learning model in Qur'an Hadith education at MTs DDI Amparita is significant. From the perspective of teacher competency in online learning, the process is running quite well as teachers have developed the ability to manage online learning through various online platforms. The implications of implementing blended learning include providing teachers with opportunities to collaborate with their peers and engage in online professional development. They can share experiences, teaching methods, and learning resources, and support each other in facing challenges and finding solutions in online learning. This model enables teachers to continuously develop their skills and knowledge through available online training and learning resources.